COMPARATIVE ANALYSIS OF NDBI AND URBAN HEAT ISLAND ACROSS FIVE WALKABLE AREA TYPOLOGIES: EVIDENCE FROM JAKARTA - Jessica Amanda Bintang Sinaga; Hayati Sari Hasibuan; Nelly Florida Riama (Universitas Sebelas Maret (UNS), 2026)
Rapid urbanization in tropical megacities such as Jakarta has intensified land surface temperatures and altered microclimates, threatening pedestrian comfort and undermining efforts to create walkable urban environments. Despite the growing emphasis on walkability in sustainable urban design, limited evidence exists on how urban heat island (UHI) effects vary across different walkable area typologies, leaving planners without typology specific guidance for climate adaptive interventions. This study aims to compare the Normalized Difference Built-up Index (NDBI) and UHI intensity across five walkable area typologies in Jakarta, such as Koja, Salemba, Dukuh Atas, Pinang Ranti, and Pasar Minggu to examine how urbanization patterns shape thermal conditions and pedestrian comfort. Multitemporal Landsat imagery from 2014, 2019, and 2024 was used to quantify urbanization, vegetation cover (NDVI), land surface temperature (LST), and UHI intensity. Results indicate that Koja exhibits the highest NDBI, lowest NDVI, and greatest UHI, reflecting intense urbanization and significant vegetation loss. Pasar Minggu follows a similar but less extreme pattern, while Salemba and Pinang Ranti maintain moderate urbanization, higher vegetation cover, and lower UHI, supporting pedestrian thermal comfort. Dukuh Atas shows intermediate conditions, balancing urban density with preserved green space. A strong positive correlation between NDBI and UHI was confirmed, indicating that urban expansion exacerbates local heating, particularly in areas with limited vegetation. These findings highlight the importance of integrating green infrastructure and density management in urban planning to mitigate UHI and improve walkability, providing actionable, typology-specific insights for climate-adaptive urban design in tropical megacities and contributing to the achievement of Sustainable Development Goal 11.